2019
DOI: 10.1002/mawe.201800130
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of spark plasma sintered titanium‐added copper/reduced graphene oxide composites

Abstract: Copper matrix composites were fabricated through mixing fixed amount of reduced graphene oxide and the different amounts of titanium. The dried copper/titanium/reduced graphene oxide mixture powders were firstly obtained by the wet‐mixing process, and then the spark plasma sintering process realized their faster densification. In the as‐sintered bulk composites, the layered reduced graphene oxide network, uniform titanium particles and copper‐titanium solid solution are observed in copper matrix. Investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…GO can form hydrogen bonds with polar groups (such as hydroxyl) on the surface of the material, and improve the mechanical properties of the material through effective stress transfer. [48][49][50] Other scholars also studied the mechanical properties of GO-reinforced CS and other composite materials, and the results all showed that GO had a reinforcing effect on composite material. 16,51 However, as the strength of the material increased, its brittleness also increased.…”
Section: Discussionmentioning
confidence: 99%
“…GO can form hydrogen bonds with polar groups (such as hydroxyl) on the surface of the material, and improve the mechanical properties of the material through effective stress transfer. [48][49][50] Other scholars also studied the mechanical properties of GO-reinforced CS and other composite materials, and the results all showed that GO had a reinforcing effect on composite material. 16,51 However, as the strength of the material increased, its brittleness also increased.…”
Section: Discussionmentioning
confidence: 99%